SISTEM PENGAMBILAN KEPUTUSAN OTOMATIS BERBASIS FUZZY UNTUK KELAYAKAN REUSE AIR DRAIN MESIN RETORT - Hadist, Mohamad Muchtarul; Sulistiyowati, Indah; Syahrorini, Syamsudduha; Falah, Agus Hayatal (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2026)
High water consumption in retort sterilization processes and the disposal of drain water with reuse potential highlight the need for an objective and automated water reuse feasibility assessment system. This study aims to develop an automated decision-making system based on Mamdani fuzzy logic to evaluate the reuse feasibility of retort drain water using turbidity, pH, and Total Dissolved Solids (TDS) parameters. The scope of this research includes the design of a multi-parameter monitoring prototype, the implementation of a food-grade-based fuzzy inference system, and the integration of decision results with automated valve control. The study adopts a research and development approach, in which sensor data are processed in real-time using a Mamdani fuzzy inference system consisting of 27 rule bases with a turbidity-based rule override mechanism. Experimental results indicate that all sensors achieve accuracy below 1%, repeatability under 0.3%, and good linearity within their operational ranges. Fuzzy logic evaluation demonstrates a decision accuracy of 100% compared to manual calculations. Testing on 30 retort drain water samples shows that 26.67% are classified as reuse, 66.67% as treatment, and 6.67% as reject, resulting in a water-saving potential of 93.33%. The proposed system effectively improves water-use efficiency, reduces operational costs, and supports sustainable practices in the food processing industry.